MENINGKATKAN KEMAMPUAN PENJUMLAHAN MELALUI MEDIA KALENDER BAGI ANAK KESULITAN BELAJAR - Maizal Padri, Zulmiyetri, Irdamurni (Universitas Negeri Padang, 2013)
The research was motivated by the problems of children learning disabilities (x) which is difficult to solve the sum. the children have difficulty in working on the summation of the results to 20, Researchers wanted to be the sum capacity can be increased by using the media calendar. The hypothesis in this study, can improve the ability of the media calendar summation for children learning difficulties. This research uses experimental approach in the form of Single Subject Research (SSR) with ABA design. As the subject of this study is children learning disabilities (x) class I in SD Negeri 15 Anduring Padang. From the research shows that the ability to sum up the results of learning disabillities for children 20 X increases. At baseline conditions before the intervention is given (A1) children are able to solve problems with the acquisition sum percentage of correct answers between 30% - 45%, after a given intervention (B) by using the media calendar percentage of correct answers increased to 40% - 80%. In the baseline condition (A2) is where the children are no longer given the longer intervention children gain percentage correct answers ranged 70% -80%. Thus previously proposed hypothesis can be accepted. It means the calendar media can improve learning difficulties summation.